Problems Encountered By Computer Science Education Student Teachers During Teaching Practice Exercise - Umakalu, Chioma Precious; Onovo, Nonso Emmanuel; Mgbeadilo, Stephanie O (Journal of Continuing and Development Education, 2023)
The main purpose of this study is to find out the problems encountered by computer science education student teachers during teaching practice exercise. Specifically, the study sought to find out the classroom management, environmental, curriculum development and instruction and supervisory problems computer science education student teachers encountered during teaching practice exercise. Four research questions guided the study. Descriptive survey research design was adopted for the study. The sample for the study was fifty-five (55) 3rd and 4th year computer science education students of Enugu State university of Science and Technology (ESUT). The sample was arrived at using census sampling techniques, this is because of the manageable size of the population. A 29 Structured questionnaire titled Problems Encountered by Student-Teachers during Teaching Practice (PESTTP) was the instrument for data collection. The overall reliability index of the instrument is 0.893 which was determined using Cronbach alpha formula. The research questions were answered using mean and standard deviation. Findings of the study revealed that computer science education student teachers during teaching practice encountered classroom management problems like; poor arrangement of the sitting position of students, controlling noise making and set inducing students. Environmental problems like; lack of tables for the student teachers, lack of chairs for the student teachers, poorly equipped libraries and poorly equipped laboratories. Curriculum developments and instruction problems like; inability of the student teachers to utilize instructional materials properly, inability of the student teachers to apply appropriate teaching skills, non-availability of relevant textbooks, writing of lesson notes, giving of written exercise, marking student exercise and supervisory problems like; supervisors spending few minutes in the class, impatience to go through the lesson notes, lack of cordial relationship between the supervisor and the student teachers, non-co-operative attitude of the regular teachers with student teachers, lack of feedback from supervisors on students’ performance to enable them take corrections and extortion of the students by some supervisors. Based on the findings of the study, it was recommended that proper attention should be given to the classroom management by the student teachers in order to achieve the specific objective at the end of the lesson in the classroom, student teachers should be provided with lodging accommodation by the practicing schools, adequate curriculum guidelines, facilities, reference materials like textbooks etc should be made available to facilitate effective and efficient teaching and learning and competent and dedicated supervisors should be used in teaching practice supervision among others.